The Role of Psychological Safety and Engagement as Mediators Between Transformational Leadership and Task Performance of Generation Z Employees in Jabodetabek Startups - Yokhebed Priscilla; Putri Mega Desiana (Universitas KH. Abdul Chalim Mojokerto, 2025)
Generation Z has become an important part of the workforce, including in the rapidly growing startup companies in Indonesia. Although known for being adaptive to technology and creative, Generation Z still faces challenges in task performance due to a lack of technical skills and low work initiative. This study aims to examine the influence of transformational leadership on the task performance of Generation Z employees in startup companies in the Greater Jakarta (Jabodetabek) area, through the mediating roles of psychological safety and employee engagement. The study uses a quantitative approach with the CB-SEM method. The respondents consist of 301 Generation Z employees working in startups in the Jabodetabek area. The results show that transformational leadership has a positive effect on task performance, psychological safety, and employee engagement. In addition to its direct effect on task performance, employee engagement also acts as a mediator in the relationship between transformational leadership and task performance. On the other hand, psychological safety is found to have no significant direct effect on task performance and does not mediate the relationship between transformational leadership and task performance. However, this variable can have a significant impact on task performance when mediated by employee engagement. These findings provide important insights for organizations seeking to improve the performance of Generation Z employees in startups in the Jabodetabek area through strengthening transformational leadership, psychological safety, and employee engagement.